TAQDĪM AND TA’KHĪR IN THE WORDS RUKŪ‘ AND SUJŪD IN AL-QUR’AN AL-KARIM - Abdurrahman, Mujib; Putri, Hurriyyah Komara (Tanzil: Jurnal Studi Al-Quran, 2025)
One of the beauties of the language of the Qur’an is taqdīm and ta’khīr, where a word is positioned first over another word for certain reasons. Usually, the pair itself is the same word and is often found in verses of the Qur’an, one of which is the words bowing and prostrating. Of the six verses that juxtapose these two words, five were found that positioned the word rukū‘ rather than sujūd, and only one verse put the word sujūd before rukū‘. So this research was made to uncover the secret behind the taqdīm of the words prostrate and ta’khīr the word rukū‘ and vice versa in terms of linguistics, namely balāghah science with its branch, namely ma‘ānī science. Meanwhile, this research is a type of research using library methods that is presented using descriptive analysis. Researchers found that the reason for the taqdīm of the word bowing down in several verses is based on the order of practice and pillars in prayer, for example, in Surah Al-Baqarah verse 125. Meanwhile, the taqdīm of the word bowing down is not because of a mistake; the order is based on the most noble practice according to Allah, namely in Surah Āli ‘Imrān verse 43. Meanwhile, the researcher’s suggestion is for readers to broaden their knowledge related to the rules of lughawiyyah in the Qur’an, especially in taqdīm and ta’khīr, as well as their causes and meanings, so as not to misunderstand and interpret the context of the Qur’an.